International longitudinal research on childhood poverty - Attawell, K (2004)
This paper details the background and activities of the Young Lives project, examining methods and tools, organisation and management, data management and analysis, and dissemination and advocacy. A number of technical documents related to the project are listed in the appendix and are available on the Young Lives website.